COMPARATIVE ANALYSIS OF MORPHOLOGICAL CHANGES IN THE LIVER IN COVID -19. (Multidisciplinary Journal of Science and Technology, 2023)
Liver injuries have been documented in patients affected by COVID-19, and commonly have mild increasing liver enzymes range from 14% to 53%. Patients with severe disease, especially those hospitalized in ICU, have shown a higher increase in transaminase enzymes than patients with mild to moderate severity. In the experiments, 43 white thoroughbred rats aged 1,3,6 months were used. These are white non-breeding rats of both sexes weighing on average about 250-300 g. The rats were fixed on a self-propelled vehicle with manual control, and in the moving vehicle, the experimental rats approached the wooden barrier and hit them on the forehead, which led to brain injury. The speed of the car was 6.7 km per hour. In the course of experiments on a traffic accident, 30 rats survived and 4 rats died. In general, i.e. macroscopic view of the liver of 1,3,6-month-old white rats, changes are observed depending on the month, varying degrees of morphological changes in the state of fatty metamorphosis in the liver cortex, consisting of lymphoid cells (hepatocytes), blood cells and epithelial cells.